2022
DOI: 10.3389/fimmu.2022.955848
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of m6A/m5C/m1A-related gene expression, immune infiltration, and sensitivity of antineoplastic drugs in glioma

Abstract: This research aims to develop a prognostic glioma marker based on m6A/m5C/m1A genes and investigate the potential role in the tumor immune microenvironment. Data for patients with glioma were downloaded from The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA). The expression of genes related to m6A/m5C/m1A was compared for normal and glioma groups. Gene Ontology and Kyoto Encyclopedia of Genes and Gene enrichment analysis of differentially expressed genes were conducted. Consistent clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…The purpose of this data collection was to assess the expression levels of m6A/m5C/m1A genes in HCC. Based on previously published literature, 5,30,32,37,38,[42][43][44] 35 m6A, 16 m5C, and 13 m1A regulator genes were selected (Table S1). The FPKM data were first transformed into transcripts per million and normalized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this data collection was to assess the expression levels of m6A/m5C/m1A genes in HCC. Based on previously published literature, 5,30,32,37,38,[42][43][44] 35 m6A, 16 m5C, and 13 m1A regulator genes were selected (Table S1). The FPKM data were first transformed into transcripts per million and normalized.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the importance of the m6A, m1A, and m5C regulatory genes in RNA modifications [31][32][33][34][35][36][37][38] and cancer progression. 30,[38][39][40] To regulate methylation, writers modify DNA through various chemical changes, such as methyl group moieties. These molecular decorations can then attract several proteins known as "readers" that identify these moieties.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this principle, our group has recently uncovered “epitranscriptomic signatures” from glioma patients’ cohorts that could be exploited to guide glioma/glioblastoma diagnosis with unmet accuracy . Far from being mere passengers in the tumorigenic process, several of these marks participate in cancer adaptation to conventional treatments and inhospitable environment. For instance, recent reports show that a dysregulation of 5-methylcytidine (m 5 C) players is associated with either oncogenic or tumor-suppressive functions according to cellular context. , The identification of RNA marks driving cancer cell adaptation to inhospitable environment and conventional treatment is essential to design appropriate therapeutic strategies, as emphasized by a growing drug discovery effort in the field . Yet, the use of sequencing data is unsuitable for this purpose, as the regulation of these marks is subject to various post-transcriptional parameters, some of which are inherent to any subcellular enzymatic system. , Target(s) discovery steps necessitate the implementation of a dedicated pipeline that would allow the accurate quantification of RNA marks on isolated RNA species.…”
Section: Introductionmentioning
confidence: 99%
“…Regretably, most studies only focus on one type of RNA modification, but ignore the potential synergistic effects of different RNA modifications on the prognosis of gliomas. Although one study 19 established a prognostic model based on m6A/m5C/m1A‐related regulators, the m7G regulators were not integrated. The potential role of m6A/m1A/m5C/m7G‐related regulators in the tumor microenvironment (TME) and prognosis for glioma patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%